Analisis Faktor-Faktor yang Mempengaruhi Produksi Telur Ayam Ras - Nina Maksimiliana Ginting; Gardis Andari; Nurliah Nurliah (AGRICOLA, 2020)
This study aims to determine the factors that affect the production of broiler breeders. Where the research was conducted purposively in Merauke District. The population was 34 breeders and the sample selection was done by purposive sampling as many as 13 breeders. Data analysis was used with multiple linear regression analysis. The results showed that the R square was 98.2%, meaning that 98.2% of the factors affecting the production of broiler egg breeders in Merauke District could be explained by variables consisting of the number of seeds, the amount of feed, the number of workers. Simultaneously, the F test is 0,000. This means that the significant value is less than 0.05 (0.000 <0.05), which means that the variable number of seeds, the amount of feed, the number of workers simultaneously or simultaneously affects the production of chicken egg breeders. Partially in the t test, only the number of seeds has an effect on the production of broilers, while the amount of feed and labor has no effect on production. Keywords: Regression, production and eggs